Primary and Secondary AI Education: Preparing Children for the Future - Zhou, Longjun (Science Insights Education Frontiers, 2025)
As a result of the expedited advancement and expanded application of artificial intelligence (AI) technology, its social and economic impacts become increasingly significant. AI is often counted as one of the major technologies in the “Fourth Industrial Revolution” (Wong et al., 2020), which is reshaping the structure and demands of the future labor markets. AI literacy, alongside reading and mathematical skills, constitutes one of the core 21st century competencies (Steinbauer et al., 2021). Hence, it is essential to integrate AI education into the primary and secondary curricula.